La memoria como eje de cambio social en la escuela (2016)
This review article corresponds to the definition and relationship that exists between memory and history, contemplating the postulates of several authors who understand the places in which it has been enrolled and the recognition of the specific characteristics of individual and collective memory. Memory has been a line of work that aims for social change and the construction of the historical memory, as well as the conceptual and pragmatic appropriation of a history of the memories, because it is necessary that education dignifies identities and strengthen efforts ofknowledge about the actual events that have transpired in the course of history